PENGEMBANGAN PERANGKAT LABORATORIUM DENGAN APLIKASI INTERFACING SENSOR CAHAYA DENGAN STOPWATCH PADA PERISTIWA GERAK PARABOLA - Sitompul, Stepanus Sahala (Jurnal Pendidikan Matematika dan IPA, 2015)
This research has the objective of knowing the application of light concept as a sensor in the moment of projectile motion using the aplication of light sensor interfacing in stopwatch. The making of light sensor device is with electronic circuits method, while the defeniting the time uses digital stopwatch. Both devices are combined to be instrument of projectile motion experiment. The result of data analysis from the graphic, the distance of the time line the curve, that it is achieved a relationship between the variable and gradient or the degree of the graphic slope of the line is 4,875. From the calculation the gradient got gravitational acceleration (g) that is 9,75 m/s2. Gravitational acceleration that is almost reading the standard gravitational acceleration, that is 9,8 m/s2 and it has only 0,05 m/s2 in difference from the research. It proves that this device can work well and stopwatch can automatically work. Keywords: Interfacing light sensor, motion projectile.